Communication mechanism, mobilization network and narrative construction of digital media in women’s rights protection movement in Iran - Shasha, Liang (International Journal Fine Arts and Creative Innovation, 2025)
In recent years, the role of digital media in social movements has become increasingly prominent, especially in countries with strict government censorship, where their information dissemination, mobilization mechanism and narrative shaping capabilities are particularly critical. The women’s rights movement in Iran has long been limited by legal and social structure, but the rise of social media has broken the traditional mode of communication and provided a new mobilization channel for women’s rights struggle. This study takes the Iranian women’s activist movement as a case to explore digital media such as How to shape the path of information dissemination, enhance the social mobilization ability, and construct the protest narrative on a global scale. This study uses a multi-level data analysis method, combined with the theory of online social movement, Theory of resource mobilization, and Frame Theory, Focusing on the "White Wednesday" Movement and # MahsaAmini Protest cases, tracking the communication characteristics of social media transmission at different stages. Through the user interaction data of Twitter, TikTok and other platforms, the diffusion mode of topic tags, information flow path and the scale of protest are analyzed. The results show that digital media plays three core roles in the women’s rights movement in Iran: First, social media breaks through the government information blockade and realizes decentralized communication, and the # MahsaAmini hashtag exceeds 200 million page views in a week, became the hot topic of global public opinion; second, the digital platform reduced the cost of protest groups, Telegram and Instagram became the main mobilization tools, the protest action expanded from Iran to more than 150 cities, and the Berlin rally was more than 80,000 people, Set one of the largest protests in Germany in recent years; third, social media shapes global protest narrative, visual symbols such as hair cutting and burning headscarf become the focus of international communication," Zan, Zendegi, Azadi (women, life, freedom) "slogan strengthens the global resonance of women’s rights protection. This study innovatively proposed the framework of "triple mechanism of digital protest", combines quantitative data and qualitative analysis, and reveals the specific mode of role of digital media in information dissemination, social mobilization and narrative shaping. At the same time, the research reveals the dynamic game of the government’s digital repression and protesters’ technology, providing a new perspective for the future research on the interaction mode of government censorship and social media struggle. The results not only enrich the theoretical research of digital media in social movements, but also provide practical inspiration for the struggle against women’s rights on a global scale.